2018
DOI: 10.1109/tnsm.2017.2785628
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Botclouds at Large Scale: A Decentralized and Robust Detection Method for Multi-Tenant Virtualized Environments

Abstract: Cloud computing has gained an important role in providing high quality and cost-effective IT services by outsourcing part of their operations to dedicated cloud providers. If intrinsic security issues of this architecture have been extensively studied, it has recently been considered as a ready-to-use platform able to perform malicious activities, thus offering new targets for indirect threats. However, its large scale, the heterogeneous and dynamic nature of the activities it executes, as well as multitenancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To lower the latency when collecting data and to ensure the isolation among network slices, in each region, we deploy a VM monitor for a network slice to collect and store metrics data of VMs in the network slice as a local database. VM monitors resort to the virtualization layer to capture resource metrics of VMs [4], [6]. The resource metrics are related with the CPU usage, memory consumption, disk read/write and network input/output.…”
Section: Three-tier Distributed Anomaly Detection Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…To lower the latency when collecting data and to ensure the isolation among network slices, in each region, we deploy a VM monitor for a network slice to collect and store metrics data of VMs in the network slice as a local database. VM monitors resort to the virtualization layer to capture resource metrics of VMs [4], [6]. The resource metrics are related with the CPU usage, memory consumption, disk read/write and network input/output.…”
Section: Three-tier Distributed Anomaly Detection Frameworkmentioning
confidence: 99%
“…[5]. Existing researches [6], [7], [8] have shown that the abnormal behaviors of VMs usually come with a significant change in resource metrics, so it is a good way to implement anomaly detection for VMs by collecting and analyzing its multi-dimensional resource metrics data. Although there have been many interesting researches for anomaly detection, including statistical and probability methods [9], [10], distance-based methods [11], [12], domain-based methods [13], [14], reconstruction-based methods [15], [16], [17], and information theory based methods [18], as classified in [19], detecting anomalies of VMs in virtualized network slicing environment still faces many challenges:…”
Section: Introductionmentioning
confidence: 99%
“…Then, in other work, we proposed an Intrusion Detection System approach for DDoS attacks launched by botclouds. Finally, we proposed a decentralized and distributed source‐based detection protocol to meet the requirements of the cloud infrastructure . However, this approach was designed only for the first case of cloud resources' abuse, namely, where an attacker creates VMs dedicated to the attack activity.…”
Section: Related Work On Botcloud Detection Approachesmentioning
confidence: 99%
“…Finally, we proposed a decentralized and distributed source-based detection protocol to meet the requirements of the cloud infrastructure. 59,60 However, this approach was designed only for the first case of cloud resources' abuse, namely, where an attacker creates VMs dedicated to the attack activity. Thus, all of the activity of the VM is malicious.…”
Section: Related Work On Botcloud Detection Approachesmentioning
confidence: 99%